2013
DOI: 10.1111/nph.12294
|View full text |Cite
|
Sign up to set email alerts
|

High resolution synchrotron imaging of wheat root hairs growing in soil and image based modelling of phosphate uptake

Abstract: SummaryRoot hairs are known to be highly important for uptake of sparingly soluble nutrients, particularly in nutrient deficient soils. Development of increasingly sophisticated mathematical models has allowed uptake characteristics to be quantified. However, modelling has been constrained by a lack of methods for imaging live root hairs growing in real soils.We developed a plant growth protocol and used Synchrotron Radiation X-ray Tomographic Microscopy (SRXTM) to uncover the three-dimensional (3D) interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
127
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(132 citation statements)
references
References 23 publications
(36 reference statements)
4
127
1
Order By: Relevance
“…Using synchrotron radiation X-ray tomographic microscopy (SRXTM) technique, Keyes et al (2013) uncovered the 3D interactions of wheat root hairs in soil (Fig. 8.4), leading to the development of a model of phosphate uptake by root hairs based on the geometry of hairs and associated soil pores.…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…Using synchrotron radiation X-ray tomographic microscopy (SRXTM) technique, Keyes et al (2013) uncovered the 3D interactions of wheat root hairs in soil (Fig. 8.4), leading to the development of a model of phosphate uptake by root hairs based on the geometry of hairs and associated soil pores.…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…This raises substantial issues with producing representative samples that can be related to higher scale systems. Recent work by Keyes et al (2013) has shown that it is possible to grow single roots in soil at a scale amenable to synchrotron imaging. By guiding roots into polymer soil chambers of diameter~4 mm using rapid-prototyped mesocosms, an intact rhizosphere (albeit for a young plant <3 weeks) can be imaged rapidly enough to suppress motion artifacts visible to the naked eye.…”
Section: Future Challenges and Opportunitiesmentioning
confidence: 99%
“…Thus, the high-detail 'gold standard' models help to make sure that simplifications do not introduce mathematical artefacts and distort scientific interpretation. However, the emergence of these models also highlights the need for more accurate and detailed characterisation of the soil chemistry; for example, buffer-power-style equilibrium characterisation of bulk soil chemistry is not very informative for the pore scale processes as described in Keyes et al (2013).…”
Section: Modelling Rhizosphere Processes: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…Most importantly, the results provided by the mathematical model need to be validated experimentally, which-in some cases-can be used to provide (refined) parameters for mathematical modelling. Apart from the geometric information that is provided by the imaging of the system, based on which the system will be modelled [15], image data can supply information on material properties that feed directly into the mathematical model. The link between greyscales in computed tomography data and bone mineralization is well established [16], which for example can be used for modelling of structural mechanics.…”
Section: Introductionmentioning
confidence: 99%